2021
DOI: 10.3390/pathogens10070877
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biofilm Formation and Prevalence of Multidrug-Resistant Strains of Staphylococcus epidermidis Isolated from Neonates with Sepsis in Southern Poland

Abstract: Staphylococcus epidermidis strains play an important role in nosocomial infections, especially in the ones associated with biofilm formation on medical devices. The paper was aimed at analyzing the mechanisms of antibiotic resistance and confirming the biofilm-forming ability among S. epidermidis strains isolated from the blood of hospitalized newborns. Genetic analysis of resistance mechanism determinants included multiplex PCR detection of mecA, ermA, ermB, ermC, msrA, and mef genes. Biofilm analysis compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(67 reference statements)
2
3
0
Order By: Relevance
“…86% of these tested strains were methicillin-resistant, of which 39% were resistant to at least four antibiotics. This problem is also pointed out in works of other researchers in which the percentage of methicillin-resistant strains was comparable to that we observed or even higher 38 40 . The strains tested in our investigations were mostly resistant to erythromycin, cefoxitin, gentamicin, and clindamycin and the values were the following: 60%, 56%, 48%, 43% respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…86% of these tested strains were methicillin-resistant, of which 39% were resistant to at least four antibiotics. This problem is also pointed out in works of other researchers in which the percentage of methicillin-resistant strains was comparable to that we observed or even higher 38 40 . The strains tested in our investigations were mostly resistant to erythromycin, cefoxitin, gentamicin, and clindamycin and the values were the following: 60%, 56%, 48%, 43% respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Macrolide resistance was the most common. A similar result was reported by Skiba-Kurek et al 38 . Of the 100 of S. epidermidis strains they tested, 67% were resistant to erythromycin.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the case of preterm isolates, four mecA and two PVL genes were isolated. Furthermore, the study of Skiba et al, 2021, reported a relatively higher percentage (89%) of the mecA gene prevalence in MRSA isolates in preterm patients [31]. Interestingly two isolates were negative for both PVL and mecA gene, suggesting the poor association of isolated MRSA with hospital-acquired MRSA.…”
Section: Discussionmentioning
confidence: 97%
“…Staphylococcus epidermidis is a microbiota that usually lives on the surface of normal human skin, and is generally not pathogenic, but can be accompanied by molecular materials entering the human body under special circumstances such as interventional treatment, and can also cause sepsis after invading blood circulation, causing serious consequences ( Skiba-Kurek et al., 2021 ). KANNAPPAN also did the same in vivo research on Staphylococcus epidermidis, and under the treatment of different combinations of geraniol and cefotaxime, it can effectively inhibit the formation of BF by pathogens ( Kannappan et al., 2019 ).…”
Section: Research On the Effect Of Traditional Chinese Medicine On Co...mentioning
confidence: 99%